Sludge Dewatering and Drying Using Microwave Heating - Omar, Wissam N. (2004)
Industrial and domestic activities produce large quantities of residual sludge. Nowadays a wide reduction of these waste volumes is necessary. Drying of the sludge which reduces its volume and mass is an important aspect for sludge management. The mechanical dewatering by pressure filters or centrifuges is not always sufficient to satisfy new environmental regulations and a thermal drying step is often needed. Microwaves are electromagnetic waves whose frequency ranges lie between that of radio waves and infrared radiation. Microwave is of rapid, volumetric and selective heating source. This study describes the evaluation of the possible use of microwave heating as a new sludge thermal treatment technology and faster sludge drying and dewatering technique.In this study, a domestic microwave oven was modified and converted into batch microwave oven with continuous weight an temperature measurement. Four different types of sludge were microwave dried under different operating condition to investigate the microwave potential in drying domestic, agriculture, and chemical sludge. The study shows that microwave drying is more efficient than convective drying up to about 20 to 36 times and ohmic heating up to 2.5 times depends on the sludge type. . Microwave still slow and not efficient at final stage of drying or at low residual moisture content. Agriculture sludge (Palm Oil sludge) was dried faster than other types under microwave energy Volume of sewage and palm oil sludge reduces up to five times by the conventional drying process, eight times by the microwave drying process and eleven times by the incineration process. Microwave treatment show more stable end product than dried sludge but less than incinerated ash in terms of the leaching properties, and it is less than the maximum limits stated by US EPA for disposal of waste to landfill. Finally, the effect of the sludge type on the gas emissions during microwave drying was investigated. Gas Emissions fluctuates during microwave treatment of sludge. CO2 and SO2 emissions increase at the end of the microwave drying process due to the increase in the temperature and the burning of the dry sludge powder.